Measurement of Cancer Health Literacy and Identification of Patients with Limited Cancer Health Literacy - Dumenci, Levent (J Health Commun, 2014)
Health literacy is related to a broad range of health outcomes. This study was designed to develop a psychometrically sound instrument designed to measure cancer health literacy along a continuum (CHLT-30), to develop another instrument designed to determine whether a patient has limited cancer health literacy (CHLT-6), and to estimate the prevalence of limited cancer health literacy. The Cancer Health Literacy Study involving 1,306 Black and White cancer patients was conducted between April 2011 and April 2013 in the Virginia Commonwealth University Massey Cancer Center and surrounding oncology clinics. A continuous latent variable modeling framework was adopted to dimensionally represent cancer health literacy, whereas discrete latent variable modeling was used to estimate the prevalence rates of limited cancer health literacy. Self confidence about engaging in health decisions was used as the primary outcome in external validation of new instruments. Results from a comprehensive analysis strongly supported the construct validity and reliability of the CHLT-30 and CHLT-6. For both instruments, measurement invariance tests ruled out item/test bias to explain gender and race/ethnicity differences in test scores. The limited cancer health literacy rate was 18%, a subpopulation consisting of overrepresented Black, undereducated, and low-income cancer patients. Overall, the results supported the conclusion that the CHLT-30 accurately measures cancer health literacy along a continuum and that the CHLT-6 efficiently identifies patients with limited cancer health literacy with high accuracy.